Pengaruh Celebrity Endorsement Terhadap Keputusan Pembelian yang Dimediasi oleh Brand Image dan Perceived Brand Quality Produk Kosmetik MS Glow - Soegeng Wahyoedi; Siska; Hery Winoto Tj (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study discusses the effect of celebrity endorsement on purchasing decisions mediated by brand image and perceived brand quality of Ms Glow cosmetic products in North Jakarta. This research was conducted using probability sampling method with the type of simple random sampling. Researchers distributed questionnaires to 100 consumer respondents of Ms Glow in North Jakarta. Data analysis using Smart PLS analysis. Celebrity endorsements by the company are able to influence the brand image of Ms Glow cosmetic products in North Jakarta. The power of celebrity endorsement can increase consumer feelings. Perceived brand quality has a positive and significant influence on purchasing decisions. So it can be said, the perceived brand quality that is felt by consumers is able to influence purchasing decisions for Ms Glow cosmetic products in North Jakarta. Brand image is not able to mediate the influence of celebrity endorsement on purchasing decisions. So it can be said that celebrity endorsements have not been able to form a good brand image in the minds of consumers, so it cannot influence the purchase decision of Ms Glow cosmetic products in North Jakarta. So it can be said, celebrity endorsements that are carried out are able to create the quality of the brand perceived by consumers will increase, so this will have an impact on purchasing decisions for Ms Glow cosmetic products in North Jakarta.